The Enterprise Value and The Financial Leverage of Manufacturing Industries in the Municipality of Bulan Sorsogon - Bongalonta, Michael B.; Bongalonta, Michelle M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research was conducted to determine and assess the financial leverage and the enterprise value of manufacturing industries in the Municipality of Bulan Sorsogon, Philippines and to establish the relationship of these two variables. This also determines the factors that influence the financial leverage decisions of the business owners. This study used mixed design. A total of 92 registered manufacturing business owners operating in the said Municipality were the primary respondents of the study. Vertical analyses and linear regression analyses were utilized. This study concludes that the manufacturing business enterprises in the Municipality of Bulan Sorsogon have significant amount of debt relative to its equity as manifested by its financial leverage. The respondents were likewise found to have a low enterprise value, with exception to company’s book value, which suggests a lower market perception of the company's worth, potentially reflecting weaker financial performance or growth prospects. Lack of personal capital, financial risk tolerance and cost of debt, cash flow stability, growth opportunities and regulatory and legal considerations were the identified factors that influence the financial leverage of the manufacturing business owners. From the results, the researcher highly recommends that manufacturing business owners may consider optimizing their capital structure to ensure an appropriate balance between debt and equity.